WEBSITE DESIGN OF FURNITURE PROMOTION THE PRIVATE ROOM USING MACROMEDIA DREAMWEAVER MX - Teni Capriyanti (Jurnal Sistem Informasi, 2008)
Use the specific website that analyzes a furniture by showing pictures of furniture itself and accompanied by information - information such as types of furniture and the price of the furniture, the writer tries to create a website about the campaign the private room furniture using Macromedia Dreamweaver MX. With this website the consumer is expected to be more varied in choose what type of furniture according to their personalities and can also freely choose furniture based on the funds or the budget they had at the time. D ari results of this study can be concluded that by using a computerized will be easier and faster in finding information.